Psychometric Properties of the Scale “5C Psychological Antecedents of Vaccination”: Ukrainian Sample - Danyliuk Ivan; Kurapov Anton; Malysheva Karine; Lytvyn Serhii (Insight: the psychological dimensions of society, 2023)
Despite the critical situation in Ukraine caused by the russian military invasion, the issue of vaccination remains a priority both during and after the war. Accordingly, attitudes toward COVID-19 vaccination are a key aspect for understanding the vaccination issue in general. The purpose of this study is to adapt and validate the Ukrainian version of the “5C Psychological Antecedents of Vaccination” scale, an instrument designed to measure psychological prerequisites for vaccination, and to investigate its psychometric properties in a Ukrainian sample. Methods. Validation was performed on a sample of 392 respondents. The psychometric properties of the scale were assessed using Cronbach’s alpha (to determine the measure of internal consistency), exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and correlation analysis with the “Multidimensional Health Locus of Control” (MHLC) scales. Results. Cronbach’s alpha values for the five subscales ranged from .65 to .84, indicating satisfactory to good internal consistency. Exploratory factor analysis (EFA) resulted in a four-factor solution. Using confirmatory factor analysis (CFA), the five-factor model was confirmed (according to the comparative fit index (CFI>.95), Tucker-Lewis index (TLI>.95), root mean square error of approximation (RMSEA>.05/RMSEA<. 08), standardized root mean square residual (SRMR<.08)), which corresponds to the original scale “5C Psychological Antecedents of Vaccination” and includes the subscales “Confidence”, “Complacency”, “Constraint”, “Calculation”, “Collective Responsibility”. The correlation analysis revealed significant correlations between the “5C Psychological Antecedents of Vaccination” scale and the “Multidimensional Health Locus of Control” (MHLC) scales, which confirms their convergent and discriminant validity. Discussion and conclusions. The Ukrainian version of the “5C Psychological Antecedents of Vaccination” scale demonstrated satisfactory psychometric properties, namely internal consistency, factor structure, convergent and discriminant validity. The Ukrainian version of the “5C Psychological Antecedents of Vaccination” scale can be used to conduct research on a Ukrainian sample.